1997
DOI: 10.1006/cbir.1996.0111
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF LECTINS IN THE KINETIDS OF TETRAHYMENA PYRIFORMIS

Abstract: Previously we described lectin-like molecules in the ciliate Tetrahymena pyriformis; by application of synthetic neoglycoconjugates it is now shown that T. pyriformis contains considerable amounts of both a beta-D-glucose- and a lactose-specific lectin. No evidence for the presence of alpha-D-mannose-, alpha-D-galactose- or of alpha-L-fucose-specific lectins could be obtained. The two lectins, identified in T. pyriformis, are associated with the kinetids. During cell division the lectins disappear or become ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Binding sites in fish skin were detected both by Danguy and Genten (1989) and Danguy et al (1991). In protozoans, glycohistochemistry has only been used on Tetrahymina piriformis, an ectocommensal of aquatic organisms (Kova`cs et al 1997): it was shown that this ciliate contains considerable amount of lectin activity specific for b-d-glucose-and lactose-motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Binding sites in fish skin were detected both by Danguy and Genten (1989) and Danguy et al (1991). In protozoans, glycohistochemistry has only been used on Tetrahymina piriformis, an ectocommensal of aquatic organisms (Kova`cs et al 1997): it was shown that this ciliate contains considerable amount of lectin activity specific for b-d-glucose-and lactose-motifs.…”
Section: Introductionmentioning
confidence: 99%